Symptoms and clinical relevance: A dilemma for clinical trials on prevention of venous thromboembolism - Bounameaux, Henri; Agnelli, Giancarlo (Thrombosis and Haemostasis, 2013)
The outcomes of thromboprophylactic trials have been debated for decades. Recently, the 9th edition of the American College of Chest Physicians (ACCP) evidence-based clinical practice guidelines based their strong recommendations only on patient-important outcomes. Practically, symptoms were considered the crucial element. Consequently, studies that primarily aimed at reducing venographic thrombi were considered less pertinent than studies that focused on symptomatic thrombosis. In the present viewpoint, we challenge the argument that “symptomatic” and “clinically relevant” are interchangeable. In particular, the case is made that asymptomatic events may be clinically relevant and that asymptomatic venographically detected thrombosis is a clinically relevant surrogate outcome for fatal pulmonary embolism.
Keywords: Prophylaxis; pulmonary embolism; thrombosis; surgery